Acute Liver Impairment in a Young, Healthy Athlete: Hypoxic Hepatitis and Rhabdomyolysis following Heat Stroke - Neville Azzopardi; Stephania Chetcuti; Jessica Sant; James Pocock (Case Reports in Gastroenterology, 2012)
Any process that substantially diminishes arterial blood flow or arterial oxygen content to the liver can result in hypoxic (ischaemic) hepatitis. 90% of hypoxic hepatitis occurs in unstable patients in intensive care units with haemodynamic failure secondary to heart failure, respiratory failure and toxic shock. The rate of in-hospital mortality in hypoxic hepatitis is very high with studies recording mortalities of 61.5%. It tends to be very uncommon in healthy, young patients with no underlying medical problems. We report here the case of a young healthy athlete who developed heat stroke associated with rhabdomyolysis and hypoxic hepatitis while he was running the final stages of a marathon. The patient required intensive care admission and inotropic support for a few hours after he was admitted with heat stroke. He underwent a rapid recovery after he was resuscitated with fluids. N-acetyl cysteine was also given during the acute stage of the hepatitis. This case highlights an uncommon case of hypoxic hepatitis in a young, healthy patient secondary to hypotension and heat stroke. Inotropic support might have precipitated the hypoxic hepatitis in this young patient.